Extensive Listening in ESP: An Experiment in the Course of “English for Tourism 2” at Dalat University - Nhue, Nguyen Truong Quynh; Van, Truong Thi My; Long, Nguyen Vu (VNU Journal of Science: Education Research, 2018)
This article presents the results of an experimental study on the practice of extensive listening strategy (EL) for the third-year students at the Faculty of Tourism, Dalat University, when studying the course of English for Specific Purposes (ESP) “English for Tourism 2”. The students of the experimental group spent eight weeks conducting searching listening materials, listening outside the classroom independently and with their team, taking weekly listening tests designed by other teams before taking the final listening test; the results of which would be used to compare with the English listening results of the control group performing traditional listening practice activities. The results of the final listening test, survey and interview responses revealed a statistically significant positive correlation between the application of EL during the course period with the English listening competence of the students, researchers also investigated the perception of these students about the application of this listening strategy. This study implies improvements in the design for future implementations of EL, including the length of practising EL activities and the enhancement of students participation in these listening activities